Effect of cottonseed biodiesel-diesel blends with dual nano additives on performance and emission: An experimental approach in a CI-Engine - Yohannes Kefale Mangesha; Ramesh Babu Nallamothu; Venkata Ramayya Ancha (Scientific African)
Biodiesel is an eco-friendly, acceptable fuel used in conventional diesel engines. The objective of this work was to examine the effect of using dual nanoparticles on emissions and performance when blended with cottonseed biodiesel and diesel fuel. Previous studies have found a single type of Nano additive, but the effects of two metal-oxides in cottonseed biodiesel haven't been measured yet. The total concentration in the blended fuel was 40, 80, and 120 ppm. CeO₂ and Al₂O₃ were each added to the B20 blend at concentrations of 20, 40, and 60 ppm. The yield of cottonseed biodiesel was 96.708≈96.71░%.Characterizations, GC–MS analysis, sonication, stability checking and the CT110 engine test rig were provided in the experimental test methods. The engine speeds were settled from 1800 to 2800 rpm at 80 % of engine load. The addition of CeO₂ and Al₂O₃ nanoparticles significantly enhanced performance, reduced emissions, and promoted fuel economy. B20-Al60Ce60 showed the best performance and lowest emissions among all blends. The Tb was recorded at 14.16016 Nm at speeds of 2000 and 2200 rpm, Pb at 5.15603 kW at 2800 rpm, and BSFC at 0.338 kg/kWh at 2800 rpm. Similarly, emission was reduced in CO by 39.23865 % at a speed of 1800 rpm, in CO₂ by 30.07 % at 2200 rpm, in HC by 65.78 % at 2000 rpm, and in NOₓ by 55.42 % at 1800 rpm. This study contributes to mitigating climate change and improving engine performance by utilizing cottonseed biodiesel with dual nanoparticles, thereby promoting fuel economy.